PHARMACOECONOMICAL ANALYSIS OF ANTI-PERIODONTOSIS DRUGS - Tolokonnikov E.G.; Aizhan S. Adekenova; Maslova O.V. (Academic Journal of Physical and Chemical Sciences, 2020)
In this work, a retrospective analysis of anti-periodontosis drugs is carried out using the methods of pharmacoeconomic analysis: analysis of the "cost of disease" (direct costs), "cost-effectiveness" for promoting the original drug "Matripin-Dent" on the pharmaceutical market. In the clinic of the Dental Institute of Kazakh National Medical University named after S.D. Asfendiyarov (Almaty), clinical trials of a new domestic phytopreparation “Dental gel Matripin-Dent” were carried out. The gel preparation was used in the complex therapy of periodontal diseases of an inflammatory and inflammatorydestructive nature. As a result of the experimental studies, it was found that "Matripin-Dent", due to the original composition of the gel composition, provides high adhesion to mucous surfaces, ensures reliable fixation of the drug on the gums, contributes to a better distribution of active components due to good absorption of the ointment base composition. It has been proven that the developed dosage form "Matripin-Dent" based on pharmacologically active compounds of Populus balsamifera L. buds and flowers, leaves, buds of Matricaria chamomilla L. has a number of advantages in comparison with the drugs existing on the pharmaceutical market used in dental practice.